Stable isotope ecology of South African kelp forests - Dyer, David Clifford (Department of Biological Sciences, 2019)
Kelp forests are some of the most productive coastal ecosystems in the world and provide numerous ecosystem goods and services. Where they occur, they play a key role in coastal ecology and local fisheries. In South Africa, Ecklonia maxima and Laminaria pallida form kelp forests which support diverse ecological communities. The species composition of these communities has been shown to be spatially variable along the South African coast, controlled by abiotic processes and species interactions. Despite their importance in the southern Benguela Current Large Marine Ecosystem (BCLME), large-scale research directed towards these habitats has largely waned over the past 30–40 years, prompting a renewed focus on these systems. Stable Isotope Analysis (SIA) is an indispensable tool for investigating food web characteristics, with particular focus on trophic structure and functioning. SIA can be used to understand the basal isotope variability in producers, determine the primary carbon sources of food webs, and investigate the spatial and temporal patterns in consumer isotope values and trophic niches. Unlike in other global kelp ecosystems, this methodology has not yet been applied to the kelp forests in South Africa. A study among eight geographically separate sites and two seasons highlights the natural variability of stable isotope values (δ13C and δ15N), at different spatial and temporal scales, within the two dominant kelp species. Additionally, stable isotope variability was investigated within and among different tissues within both kelp species. Within a kelp plant, δ13C values had a range of 1.65‰ for E. maxima and 1.52‰ for L. pallida. The δ15N values had a range of 3.75‰ for E. maxima and 4.21‰ for L. pallida. There were also consistent variability patterns along the length of a single frond in both species, for both isotopes. Among the localities, E. maxima and L. pallida were highly variable with ranges in δ13C (9.37‰ and 11.22‰) and δ15N (3.44‰ and 4.51‰) for the two species respectively. The δ13C values of L. pallida and E. maxima displayed a clear pattern coinciding with depth, particularly for L. pallida. Within-site variability was a major contributor to the overall spatial variability for both species. This provides further evidence for the importance of understanding basal variability of stable isotope values when determining the carbon sources of bottom-up controlled ecosystems. Variability in particulate organic matter (POM) composition is hypothesized to be related to upwelling processes in, and around, a typical west coast kelp forest. Various variables were used to characterise the composition, and determine the dynamics, of the POM along two transects (alongshore and off-shore) originating within a kelp forest. SIA was employed to estimate the contribution of kelp-derived detritus (KDD) to the POM present in the water column, using a unique approach for isolating phytoplankton and kelp end-member values. Under upwelling conditions, stable isotope analyses confirmed the dominance (>70%) of kelp detritus in POM samples, even at distances of 7.5 km off-shore. Under downwelling conditions, however, phytoplankton was dominant (>60%) along both transects. This study therefore highlights the importance of coastal processes such as upwelling for controlling the composition of POM in kelp forests, as well as illustrating how the natural variability in POM composition created by upwelling processes can be used to gather POM endmember isotope values. Three ecologically distinct kelp forest communities were investigated using a combination of SIA and community-wide niche metrics ('Layman metrics’ and Bayesian inferences). Three kelp forests, with differing community composition were selected, including a west coast kelp forest, a False Bay kelp forest and a lobster-invaded kelp forest located east of Cape Hangklip at Betty’s Bay. Temporal and spatial variability in stable isotope values was identified in producer and consumer stable isotope values, but was variable among species. Community-wide metrics showed clear seasonal patterns, but despite large differences in community structure, metrics were not vastly different among sites. Seasonal variability was the largest observable trend in metrics at all sites. Community niche areas showed a high degree of overlap (80–95%) further illustrating the similarity among sites and seasons. These findings are largely contrary to expected patterns from community composition data. Trophic position and isotope niche of the West Coast Rock Lobster (Jasus lalandii) was determined at three ecologically different kelp forest habitats, located in Marine Protected Areas in south-western South Africa. Temporal and spatial variability in trophic position and niche size were detected. The stable isotope niche and trophic position of lobsters at Betty’s Bay were markedly different from those at Oudekraal and Bordjiesrif, with the summer niche being distinct (0% overlap). Trophic position was lowest at the lobster-invaded Betty’s Bay (2.52) and highest at Bordjiesrif (3.16). Similarly, the isotope niche of Jasus lalandii was significantly constricted at Betty’s Bay compared to the other two study sites. Primarily, these results show that in the region where these lobsters have invaded, the trophic niche is considerably constricted. This likely to be a consequence of the higher densities of lobsters in this area. These findings highlight the influence of the lobster invasion on Jasus lalandii itself, adding to the already published ecological effects on the kelp forest ecosystem as a whole. These findings also highlight the differences in trophic niche of this species, despite the overall community niche showing little difference among sites. The findings of this thesis provide estimates of the variability in stable isotope values of kelp forest seaweeds and consumers, as well as addressing the importance of ocean processes such as upwelling in controlling POM composition in kelp forests. Additionally, the trophic niche of a key kelp forest predator was characterised in ecologically different kelp forests, providing evidence of the effect of community structure on the niche of this species. This is the first concerted research effort into the stable isotope ecology of South African kelp forests, providing an updated look at the ecology of these important ecosystems, and serves as a foundation for future studies of this type.